SEHARI BERBAHASA ASING SEBAGAI STRATEGI BELAJAR MEMAHAMI POTENSI PARIWISATA LOKAL - Maria Martha Nikijuluw; Hendry Latuheru; Roland Alfons (German für Gesellschaft (J-Gefüge), 2023)
Language Studies Centre (called as PSB) of Pattimura University (Unpatti) organized community service activities (PkM), with the theme "A Day in Foreign Languages as a Learning Strategy to Understand the Potential of Local Tourism". This PkM activity has two goals: (a) students' motivation to learn English in the field of local tourism potential, based on understanding and practicing learning to become a tour guide in Nuniali congregation (Jemaat GPM Nuniali), and (b) try out of online foreign language courses (Dutch and English) through ZOOM. With a descriptive analysis approach through a questionnaire instrument, it was found that all participants liked English (a total of 36 participants or 100%), while the themes most liked by participants were: (1) waterfall tourism with 33 responses yes or like; (2) the history of the origin of the village (24 responses); (3) travelling in West Seram (SBB) with a total response yes of 23 people. Meanwhile, the most preferred learning activity by participants was direct practice in tourist spot as 25 responses (69.4%) and if it is interpreted according to the professional experience of the PkM Team in relation to tourist guiding, shown that there was already a potential of almost 70% of the number of responses liked the tourist guide profession. Meanwhile, the trial of an online foreign language course via Zoom at the Nuniali congregation showed that the church (the priest of congregational) could play an active role in finding solutions for the absence of an English teacher at the Christian Schools (called as YPPK) by means of providing an English language course/solution via ZOOM